Structure elucidation by NMR in organic chemistry : a practical guide - Breitmaier, E.; Wade, Julia (Chichester ; New York : John Wiley and Sons, 1993)
This book is about: Recognition of structural fragments by NMR; Skeletal structure; ...
Keywords: Organic compounds; Structure; Organic compounds -- Structure; Nuclear magnetic resonance spectroscopy